Efektivitas Kombinasi Pelaksanaan Labor Dance dan Terapi White Noise dalam Penurunan Intensitas Nyeri Persalinan Kala I Fase Aktif - Gusti Ayu Suastika Dewi; I Gusti Agung Manik Karuniadi; Ni Made Egar Adhiestiani (STIKes Hamzar, 2026)
The majority of women will experience pain during the childbirth process as a result of uterine contractions, and each mother in labor will interpret pain differently from the same stimulus based on the pain threshold they feel during the birthing process. Severe labor pain that is not appropriately managed will interfere with the smoothness of the labor process, thus pain management techniques such as white noise and labor dance are required. The purpose of this study was to determine how well the combination of labor dance and white noise therapy worked in reducing the intensity of labor pain during the first active phase in the PONEK ward of Mangusada Regional Hospital. This study used a quantitative research approach, a quasi-experimental research design, a nonequivalent control group design, and an accidental sampling strategy involving 30 giving birth women during the first active phase. The participants were placed into two groups: the control and the intervention group. The Wilcoxon Signed Test was used to compare the outcomes of the pre-test and post-test, and the Mann Whitney U-Test was used to compare the control and the intervention group. There was a difference in pain intensity between mothers in the first active phase of labor in the control group after being given routine care and the intervention group after being given a combination of labor dance and white noise therapy with a p value = 0.016 < 0.05 so it can be concluded that the combination of labor dance and white noise therapy was effective in reducing labor pain intensity inthe first active phase in the PONEK ward of Mangusada Regional Hospital. It is intended that the combination of labor dance and white noise therapy would be prescribed as a complementary therapy and used to alleviate labor pain, allowing labor to proceed gently and smoothly.